تأثير وحدات تدريبية مقترحة بطرق الاسترخاء العضلي في التقليل من قلق المنافسة لدى لاعبي كرة القدم ( فئة أقل من 19 سنة ) - لعبادي, الصديق (My University, 2020)
أهداف الدراسة: -التعرف على أثر الوحدات التدريبية المقترحة بطرق الاسترخاء العضلي في التقليل من قلق المنافسة لدى لاعبي كرة القدم. -معرفة ما اذا كانت هناك فروق ذات دلالة احصائية في درجة اللاعبين على مقياس قلق المنافسة اثناء التطبيق القبلي للبرنامج التدريبي المقترح -معرفة ما اذا كانت هناك فروق ذات دلالة احصائية في درجة اللاعبين على مقياس قلق المنافسة اثناء التطبيق البعدي للبرنامج التدريبي المقترح مشكلة الدراسة: هل للوحدات التدريبية المقترحة بطرق الاسترخاء العضلي أثر في التقليل من قلق المنافسة لدى لاعبي كرة القدم ( فئة أقل من 19 سنة) فرضيات الدراسة: -لا توجد فروق ذات دلالة إحصائية في درجة اللاعبين على مقياس قلق المنافسة اثناء التطبيق القبلي للبرنامج التدريبي المقترح -توجد فروق ذات دلالة إحصائية في درجة اللاعبين على مقياس قلق المنافسة اثناء التطبيق البعدي للبرنامج التدريبي المقترح عينة الدراسة: فريق اتحاد الرياضي العناصر (فئة أقل من 19 سنة) المنهج المتبع في الدراسة: استخدام الباحث المنهج التجريبي لملائمته موضوع الدراسة. أدوات الدراسة: استبيان – برنامج تدريبي. كلمات المفاتيح: وحدات تدريبية، الاسترخاء العضلي، قلق المنافسة، كرة القدم، فئة أقل من 19 سنة The effect of suggested training modules on muscle relaxation methods on reducing competition anxiety among soccer players (under 19 years old) Objectives of the study: Knowing the effect of the proposed training units on muscle relaxation methods in reducing competition anxiety among soccer players. -To see if there are statistically significant differences on the degree of players on the scale of competition anxiety during the pre-application of the proposed training program - See if there are statistically significant differences in the degree of players on the scale of competition anxiety during the post-implementation of the proposed training program the study Problem: Do the suggested training modules in muscle relaxation methods have an effect on reducing competition anxiety among soccer players (under 19 years of age)? Study hypotheses: -There are no statistically significant differences in the degree of players on the scale of competition anxiety during the pre-application of the proposed training program -There are statistically significant differences in the degree of players on the scale of competition anxiety during the post-implementation of the proposed training program The study sample: Football players for Al-Ittihad Al-Riyadi team (under 19 years old) The approach followed in the study: The researcher used the experimental approach to its relevance to the subject of the study. Study tools: Questionnaire - training program. Keywords: Training modules, muscle relaxation, competition anxiety, soccer, under 19 years old.
Keywords: الاسترخاء العضلي; قلق المنافسة; كرة القدم; وحدات تدريبية; Training modules; muscle relaxation